2023
DOI: 10.15540/nr.10.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-neuro-biological Correlates of Beta Activity

Abstract: Chronic stress and anxiety in everyday life can lead to sympathetic hyperactivity. This can be observed as behavioral, chemical, and neurological changes, including increased rumination, anxiety, and depression, and chemical changes in biological markers like homocysteine. In the EEG, increased beta (13-30 Hz) wave activity, especially high beta (> 20 Hz) has long been noted in anxiety states. However, recent research indicates that low beta waves (13-20 Hz) may play a role as well. The current paper presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
2
6
1
Order By: Relevance
“…As for qEEG, there was a significant difference in the CSD of the left dlPFC in the β2 band between the two groups, suggesting that MOT intervention caused the change in dlPFC function. Previous qEEG studies have correlated high beta activity with anxiety [65,66] and average low beta relative power wave activity with improvements in anxiety and depression [67]. Thus, the results of the qEEG study, which did not specify brain regions and used a simple method, reported a correlation between excessive high beta activity and symptoms of anxiety and depression, which is not consistent with the results of our current study.…”
Section: Discussioncontrasting
confidence: 99%
“…As for qEEG, there was a significant difference in the CSD of the left dlPFC in the β2 band between the two groups, suggesting that MOT intervention caused the change in dlPFC function. Previous qEEG studies have correlated high beta activity with anxiety [65,66] and average low beta relative power wave activity with improvements in anxiety and depression [67]. Thus, the results of the qEEG study, which did not specify brain regions and used a simple method, reported a correlation between excessive high beta activity and symptoms of anxiety and depression, which is not consistent with the results of our current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on the detailed methods previously described, we present a summary of the materials and methods herein (Leaf, Turner, Wasserman, et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Answering this call, we implemented the Neurocycle app as a planned and guided process that models how to optimize the science of habit formation and automaticity in mental health interventions. The Neurocycle has been evaluated as an evidencebased intervention for mental health in clinical trials, using a psychoneurobiological approach, assessing participants' psychosocial reports of mental health wellness, energy patterns in the brain, and hematological measures (Leaf, Turner, Wasserman, et al, 2023).…”
Section: The Need For a Psychoneurobiological Approach In Automaticit...mentioning
confidence: 99%
See 2 more Smart Citations